Love & friendship [videorecording (DVD)] - Beckinsale, Kate; Sevigny, Chloë; Samuel, Xavier, 1983-; Austen, Jane, 1775-1817 (Sony Pictures Home Entertainment, 2016)
The beautiful widow Susan Vernon has come to the estate of her in-laws to wait out colorful rumors about her dalliances circulating through polite society. Whilst there, she decides to secure a husband for herself and her rather reluctant debutante daughter, Frederica.